From awareness to action: green practices in the Iberian Peninsula’s hospitality sector - Cunha, M.N.; Nogueira, S. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2025)
This research critically examines the extent to which hospitality enterprises operationalize sustainability within the distinctive context of UNESCO biosphere reserve. Beyond mapping establishments profile, the study interrogates the scope and depth of green practices, spanning energy efficiency, water conservation, waste management, and sustainable procurement, while simultaneously evaluating the awareness and perceptions of both employees and consumers. Employing a descriptive research design, survey data were collected from employees and customers across 30 establishments. Findings demonstrate that the sector is largely characterized by micro to small enterprises with limited manpower (typically 4–6 employees) and relatively recent market presence (4–7 years). Sustainability practices were most consistently institutionalized in waste management (Mean (M) = 4.90), water conservation (M = 4.74), energy efficiency (M = 4.67), and sustainable purchasing (M = 4.69). By contrast, capital-intensive strategies, such as solar energy systems and sustainable interior design, remain marginal. Employees exhibited high levels of awareness (M = 3.87) and strong endorsement of sustainability (M = 4.46), while customers reported encountering practices only “Often” or “Sometimes,” indicating a perceptual gap between organizational intent and consumer recognition. The study contributes to the scholarly discourse on sustainable hospitality by evidencing the predominance of cost-effective, behaviourally driven initiatives over technologically advanced interventions. It argues for the necessity of targeted training, financial incentives, and policy alignment to foster a systemic transition towards more robust sustainability frameworks in the Iberian Peninsula.